Asymmetric monetary policy towards the stock market: A DSGE approach - Søren Hove Ravn (Danmarks Nationalbank, 2012)
In the aftermath of the financial crisis, it has been argued that a guideline for future policy should be to take the 'a' out of 'asymmetry' in the way monetary policy deals with asset price movements. Recent empirical evidence has suggested that the Federal Reserve may have followed an asymmetric policy towards the stock market in the pre-crisis period. The present paper studies the effects of such a policy in a DSGE model. The asymmetric policy rule introduces an important non-linearity into the model: Booms in output and inflation will tend to be amplified, while recessions will be dampened. I further investigate to what extent an asymmetric stock price reaction could be motivated by the desire of policymakers to correct for inherent asymmetries in the way stock price movements affect the macroeconomy.
Keywords: E13; E32; E44; E52; E58; 330; Asymmetries; Monetary Policy; Asset Prices; DSGE Modelling; Geldpolitik; Börsenkurs; Dynamisches Gleichgewicht; Theorie